Aluminum ethoxide composite polymer electrolyte membrane, preparation method of aluminum ethoxide composite polymer electrolyte membrane, application of aluminum ethoxide composite polymer electrolyte membrane in battery and assembly process of battery

By using aluminum ethanol composite polymer electrolyte membrane in lithium metal batteries, the dual coordination mechanism of aluminum atoms and PEO polymers and the direct enhanced interface compatibility between nanowire fillers are solved, and the problems of uneven conduction of lithium ion and difficulty in controlling dendrite growth are achieved, and the efficient cycle stability and high-temperature performance of the battery are achieved.

CN119650833AActive Publication Date: 2025-03-18SUN YAT SEN UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411836431.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-18
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

In existing lithium metal batteries, the interface compatibility of solid polymer electrolytes is poor with that of ceramic fillers, resulting in uneven conduction of lithium ions and difficulty in controlling dendrites' growth, which affects the safety and performance of the battery.

Method used

The aluminum ethanol composite polymer electrolyte membrane is used. This membrane enhances the orderly conduction of lithium ions through the dual coordination mechanism between aluminum atoms and polyethylene oxide (PEO) polymer, and directly enhances interface compatibility through the selective dealloyment method of nanowire fillers.

Benefits of technology

It realizes fast and orderly conduction of lithium ions, improves conductivity and interface compatibility, significantly inhibits the formation of dendrites, and improves the cycle stability and high-temperature performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650833A_ABST
    Figure CN119650833A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of chemical batteries, in particular to an aluminum ethoxide composite polymer electrolyte membrane, a preparation method of the aluminum ethoxide composite polymer electrolyte membrane, application of the aluminum ethoxide composite polymer electrolyte membrane in a battery and an assembly process of the battery. The aluminum ethoxide composite polymer electrolyte membrane comprises a polymer and aluminum ethoxide, the structure of the polymer contains ester groups or / and ether bonds; the polymer is polyethylene oxide or a polyethylene oxide derivative; the polyethylene oxide derivative is obtained by carrying out photopolymerization on a small molecular monomer. When the aluminum ethoxide composite polymer electrolyte membrane is applied to a battery, the interfacial compatibility is enhanced, rapid and ordered transmission can be realized, and the cycling stability is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of chemical batteries, and in particular to an ethanol aluminum composite polymer electrolyte membrane, a preparation method thereof, an application thereof in a battery, and an assembly process of a battery. Background Art

[0002] Lithium metal batteries (LMBs) are widely considered to be ideal for next-generation energy storage systems due to their ultra-high energy density. However, the practical application of LMBs is severely limited in terms of safety due to the difficulty in controlling the growth of lithium dendrites when circulating in organic liquid electrolytes (LEs). To address this problem, solid (such as ceramics and solid polymers) and quasi-solid (such as gel polymers) electrolytes are seen as promising alternatives to improve the safety and performance of LMBs. Although ceramic electrolytes are believed to prevent lithium dendrite penetration due to their mechanical rigidity, some studies have shown that lithium dendrites may grow along the grain boundaries of ceramic electrolytes. In addition, there is a high and unstable interface resistance between solid electrodes and ceramic electrolytes, resulting in slow interfacial charge transfer. In contrast, solid polymer electrolytes can be used to improve their interfacial compatibility with solid electrodes.

[0003] Among various polymer materials, solid polymer electrolytes (SPEs) based on polyethylene oxide (PEO) have long been a research focus. However, they not only have low ionic conductivity, low mechanical strength and insufficient antioxidant properties at room temperature, which limits their application in LMBs. In the current prior art, in order to improve the performance of PEO-based SPEs at room temperature, plasticizers, i.e., small molecule liquid solvents, are usually added to the polymer matrix to prepare PEO-based gel polymer electrolytes (GPEs) with high ionic conductivity. However, the addition of plasticizers will weaken the mechanical strength of GPE and make it difficult to inhibit the growth of lithium dendrites. To this end, a common method for improving ionic conductivity and polymer electrolyte stability is to add ceramic fillers to the PEO matrix to form a composite SPE. However, due to the differences in structure and performance between inorganic fillers and organic polymers, the interface compatibility between the two is poor, which not only increases the internal interface impedance, but also easily leads to filler aggregation, hinders the construction of lithium ion conduction channels, and ultimately leads to uneven deposition of lithium ions at the negative electrode.

[0004] In order to improve the interfacial compatibility between the organic matrix and the filler, current research mainly forms effective connections through chemical bonds. For example, the team led by Academician Zhang Suojiang of the Chinese Academy of Sciences used the silane coupling agent (3-chloropropyl) trimethoxysilane (CTMS) as a "bridge" to connect the ceramic filler LGPS with polyethylene glycol (PEG) through chemical bonds, constructing a "high-speed channel" for lithium ion transmission, and compounding it with PEO and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to prepare a composite solid electrolyte with excellent performance. [1] Archer et al. prepared a soft colloidal glass composite solid electrolyte by functionalizing PEO with amino groups to achieve covalent connection with SiO2 inorganic nanoparticles. [2] In addition, Professor Robert KYLi used LiOH / Li2CO3 contaminants on the surface of LLZTO as initiators to introduce ethylene carbonate and generate ion-conductive ether oxygen oligomers through ring-opening polymerization, thereby improving the compatibility of particles with the PEO matrix. [3] Although the above studies have improved the interfacial compatibility by adding organic small molecules or organic functional groups as a "bridge", the operation is complex and the conditions are harsh, and it is impossible to achieve direct bonding between the filler and the organic matrix.

[0005] For example, Chinese patent CN117467164A discloses a polymer solution, gel electrolyte, sodium ion battery, gel polymer separator, and preparation method, which introduces nano-Si / Ti oxide compounds by adopting an in-situ hydrolysis and polycondensation method, and has the advantages of improving the ionic conductivity and interface compatibility of the gel polymer electrolyte. However, the method for increasing compatibility is complicated and introduces other metal impurities.

[0006] In addition, due to the low oxidative decomposition potential and complicated lithium ion transport pathway of PEO-based SPE, it is difficult to combine with LiNi 0.6 Co 0.2 Mn 0.2 The compatibility of NCM cathodes with high voltage cathodes such as O2 (NCM622) has become a major obstacle to commercial applications. Although the direct contact between NCM cathode and PEO can be avoided by adding a coating on the cathode surface or compounding PEO with polyacrylonitrile (PAN), or the intrinsic structural stability of PEO can be enhanced through molecular structure design to adapt to NCM cathode, it is still a major challenge to simultaneously enhance the stability of the electrode / electrolyte interface and regulate the ion conduction behavior of the composite polymer electrolyte through molecular structure engineering design.

[0007] Therefore, there is an urgent need to provide an electrolyte membrane with a simple preparation method, direct bonding between fillers and organic matrices, high interface compatibility, high voltage matching, and significant inhibition of dendrite formation, and to apply it to batteries.

[0008] References:

[0009] [1]Pan K, Zhang L, Qian W, et al.A Flexible Ceramic / Polymer HybridSolidElectrolyte for Solid-State Lithium Metal Batteries.2020,32(17):e2000399.

[0010] [2]Choudhury S,Stalin S,Deng Y,et al.Soft colloidal glasses as solid-stateelectrolytes.2018,30(17):5996-6004.

[0011] [3]He K,ChengS.H,HuJ,et al.In-Situ Intermolecular Interaction inComposite Polymer Electrolyte for Ultralong Life Quasi-Solid-StateLithiumMetal Batteries.2021,133:12223-12230. Summary of the invention

[0012] Based on the deficiencies of the prior art, the present invention aims to provide an electrolyte membrane with a simple preparation method, direct bonding between fillers and organic matrix, high interface compatibility, high voltage matching, and significant inhibition of dendrite formation, and its application in batteries.

[0013] In order to achieve the above object, the present invention adopts the following technical solutions:

[0014] In one aspect, the present invention provides an aluminum ethoxide composite polymer electrolyte membrane, wherein the aluminum ethoxide composite polymer electrolyte membrane comprises a polymer and aluminum ethoxide;

[0015] The polymer is a polymer containing an ester group and / or an ether bond in its structure; the polymer is polyethylene oxide or a polyethylene oxide derivative; the ethanol aluminum can be obtained by commercial purchase or self-preparation; the polyethylene oxide derivative is obtained by photopolymerization of small molecule monomers.

[0016] Preferably, the small molecule monomer is selected from one or more of polyethylene glycol diacrylate, triethylene glycol diacrylate, polyethylene glycol diacrylate, tetraethylene glycol diacrylate, 1,3-dioxolane, polyethylene glycol dimethyl ether, ε-caprolactone and ethoxylated trimethylolpropane triacrylate.

[0017] Preferably, the polymer of polyethylene oxide is PEO.

[0018] More preferably, the small molecule monomer is selected from PEGDA, TEGDA, TEPTA and ε-CL.

[0019] In another aspect, the present invention also provides a method for preparing the aluminum ethanol composite polymer electrolyte membrane, comprising the following steps:

[0020] A. Synthesis of Aluminum Ethanol Film

[0021] (1) Aluminum powder and metal powder are mixed and melted to obtain molten alloy sheets;

[0022] (2) cooling the alloy sheet in step (1), and then reacting with anhydrous ethanol to obtain ethanol aluminum gel;

[0023] (3) washing the byproducts and filtering the ethoxide aluminum gel obtained in step (2) to obtain an ethoxide aluminum film;

[0024] B. Synthesis of Aluminum Ethoxide Composite Polymer Electrolyte Membrane

[0025] S1. In an inert atmosphere, a polymer monomer and a photoinitiator are mixed to obtain a mixed solution, and then the mixed solution and a basic electrolyte are mixed and stirred to obtain a photocurable precursor solution;

[0026] S2. Placing the aluminum ethanol film obtained in step A on the negative electrode, dripping the photocurable precursor solution obtained in step S1, and irradiating with ultraviolet light or drying to obtain the aluminum ethanol composite polymer electrolyte membrane.

[0027] Preferably, the ratio of the aluminum powder to the lithium powder in step (1) of A is 2.5-3.5:0.85; the melting temperature is 750-850° C., and the melting time is 15-25 min.

[0028] More preferably, the ratio of the aluminum powder to the lithium powder in step (1) in A is 3:0.85; the melting temperature is 800° C. and the melting time is 20 min.

[0029] Preferably, the mass volume ratio of the alloy sheet to anhydrous ethanol in step (2) in A is 0.11-0.12 g: 15-25 mL; and the reaction time is 25-35 h.

[0030] More preferably, the mass volume ratio of the alloy sheet to anhydrous ethanol in step (2) in A is 0.115 g:20 mL; and the reaction time is 30 h.

[0031] Preferably, the photoinitiator in step B (1) is phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (BAPO).

[0032] Preferably, the mass fraction of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide in the above monomer is 1 wt %.

[0033] Preferably, the basic electrolyte solution in step S1 in B comprises an electrolyte salt and a solvent.

[0034] Preferably, the weight ratio of the mixed solution to the basic electrolyte is 1-10:10.

[0035] Preferably, the ultraviolet light irradiation time in step S1 in B is 20 seconds.

[0036] Preferably, the drying in step S2 in B is carried out at 50° C. for 4 hours.

[0037] Preferably, the amount of the photoactivated precursor dripped in step S2 in B is 20-30 μL.

[0038] In another aspect, the present invention also provides the use of the above-mentioned ethanol aluminum composite polymer electrolyte membrane in the preparation of a battery.

[0039] Preferably, the battery is a lithium battery or a sodium battery.

[0040] Preferably, the battery consists of a negative electrode, an ethanol aluminum composite polymer electrolyte membrane and a positive electrode.

[0041] In another aspect, the present invention further provides an assembly process of the above-mentioned battery, characterized in that it comprises the following steps:

[0042] (1) combining the prepared ethanol aluminum composite polymer electrolyte membrane with the negative electrode;

[0043] (2) Using commercial cathode as cathode material;

[0044] (3) Assemble and obtain the battery.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] (1) The aluminum ethoxide of the present invention contains aluminum atoms with abundant unsaturated coordination sites, which can act as Lewis acid sites to coordinate with oxygen atoms in OC=O and COC of PEO and PEO-like derived polymer matrices, while OC=O and COC in PEO and PEO-like derived polymer matrices will coordinate with Li+, and oxygen atoms in aluminum ethoxide will also coordinate with Li+. This dual coordination mechanism greatly enhances the orderly conduction of lithium ions at the Al(EtO)3-PEO interface, improves lithium ion conductivity, and realizes rapid and orderly transmission.

[0047] (2) The nanowire filler used in the present invention is not a traditional ceramic nanowire, but an amphoteric metal alkoxide. The ethanol aluminum nanowire used in the present invention is prepared by a selective dealloying method and has aluminum atoms with abundant unsaturated coordination sites. These sites can effectively coordinate with the PEO polymer chain to directly enhance the interfacial compatibility without the need for a coupling agent. This method is different from other reported methods for PEO-based composite electrolyte systems.

[0048] (3) The battery technology of the present invention exhibits stable cycle performance within a wide temperature range of -20°C to 60°C. This feature has significant advantages in low-temperature applications and expands the application scenarios of the battery.

[0049] (4) The ethanol aluminum composite polymer electrolyte membrane prepared by the present invention can match high-voltage positive electrode materials and can support high-voltage commercial positive electrodes to maintain long-cycle stability. This feature makes it have important application potential in improving battery capacity and energy density, and is suitable for the development of high-energy density batteries. The ethanol aluminum composite polymer electrolyte membrane prepared by the present invention can be applied to all positive electrode materials of lithium / sodium batteries, such as sodium nickel iron manganese oxide, sodium vanadium phosphate, etc.

[0050] (5) The Al(EtO)3-PEO system of the present invention can generate an aluminum-based electrolyte interface in situ on the surface of the positive and negative electrodes, which includes aluminum and its derivatives with high mechanical strength and ionic conductivity, effectively inhibiting the interface side reactions. The aluminum-based electrolyte interface layer not only improves the electrode / electrolyte interface stability, but also prevents phase change and stress cracking of the high-nickel layered positive electrode material, thereby achieving excellent cycle stability and high rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 The figures are cycle test diagrams of the batteries of Example 1 and Comparative Example 1;

[0052] Among them, the unfilled squares and triangles are the Coulomb efficiency diagrams;

[0053] Figure 2 The figures are cycle test diagrams of the batteries of Application Example 2 and Comparative Example 2;

[0054] Among them, the unfilled squares and triangles are the Coulomb efficiency diagrams;

[0055] Figure 3 It is a cycle test diagram of the battery of application example 3 and application comparative example 3;

[0056] Among them, the unfilled squares and triangles are the Coulomb efficiency diagrams;

[0057] Figure 4 This is a cycle test diagram of the battery of Application Example 4;

[0058] Among them, the unfilled square is the Coulomb efficiency diagram;

[0059] Figure 5 It is a cycle test diagram of the battery of Application Example 5 and Application Comparative Example 4;

[0060] The unfilled squares and triangles are the Coulomb efficiency plots. DETAILED DESCRIPTION

[0061] The present invention is further described in detail below with reference to specific embodiments.

[0062] Example 1

[0063] A. Preparation method of Al(EtO)3 film

[0064] (1) 0.3 g of aluminum powder and 0.085 g of lithium powder were weighed and uniformly mixed in a graphite crucible to obtain a mixture; the mixture was placed in a muffle furnace, heated at 800° C. for 20 min, then quickly taken out and flattened with a graphite column, and cooled to obtain a LiAl alloy.

[0065] (2) Synthesis of Al(EtO)3: 0.115 g of LiAl alloy was reacted with 20 mL of anhydrous ethanol for 30 h to obtain a uniform Al(EtO)3 gel.

[0066] (3) The gel obtained in step (2) was washed three times with 10 mL of anhydrous ethanol to remove soluble lithium ethoxide, and 2 mL of the gel was filtered to obtain a smooth Al(EtO)3 film, which was then cut into small discs with a diameter of 16 mm.

[0067] B. A method for preparing an ethanol aluminum composite polymer electrolyte membrane

[0068] S1. Under an inert atmosphere, PEGDA (mixed with 1 wt% of photoinitiator BAPO) and basic lithium battery electrolyte (1 mol LiPF6 in a mixed solution of EC, DMC and EMC (the volume ratio of EC: DMC: EMC is 1:1:1) are mixed at a ratio of 1.5:10 (w / w) and stirred overnight to form a uniform solution to obtain a photocurable precursor solution.

[0069] The mass ratio of PEGDA (mixed with 1 wt % of photoinitiator BAPO) to the basic electrolyte is 1.5:10.

[0070] S2. Inject 20 μL of photocurable precursor solution onto the Al(EtO)3 film and cure it under ultraviolet radiation for 20 seconds to obtain a composite polymer electrolyte (Al(EtO)3-PEGDA).

[0071] Example 2

[0072] A. Grinding of commercial aluminum ethanol powder:

[0073] 1 g of aluminum ethoxide powder purchased from MacLean Reagent Network (Cat. No. A831038) was weighed into a mortar and ground for half an hour.

[0074] B. A method for preparing an ethanol aluminum composite polymer electrolyte membrane

[0075] S1. Under an inert atmosphere, TEPTA (mixed with 1 wt% of photoinitiator BAPO) and basic lithium battery electrolyte (a mixed solution of 1 mol LiPF6 in EC, DMC and EMC (the volume ratio of EC: DMC: EMC is 1:1:1.2) and ethanol aluminum powder are mixed in a ratio of 1.5:10:0.3 (w / w / w), and stirred overnight to form a uniform solution to obtain a photocurable precursor solution.

[0076] The mass ratio of TEPTA (mixed with 1 wt % of photoinitiator BAPO) to the basic electrolyte is 1.5:10.

[0077] S2. Add 30 μL of the photocurable precursor solution onto the lithium metal negative electrode and cure it under ultraviolet radiation for 20 seconds to obtain a composite gel polymer electrolyte (Al(EtO)3-TEPTA).

[0078] Example 3

[0079] A. Preparation method of Al(EtO)3 film

[0080] (1) 0.3 g of aluminum powder and 0.085 g of lithium powder were weighed and uniformly mixed in a graphite crucible to obtain a mixture; the mixture was placed in a muffle furnace, heated at 800° C. for 20 min, then quickly taken out and flattened with a graphite column, and cooled to obtain a LiAl alloy.

[0081] (2) Synthesis of Al(EtO)3: 0.115 g of LiAl alloy was reacted with 20 mL of anhydrous ethanol for 30 h to obtain uniform Al(EtO)3.

[0082] (3) The obtained gel was washed three times with 10 mL of anhydrous ethanol to remove soluble lithium ethoxide. 2 mL of the gel was taken and filtered to obtain a smooth Al(EtO)3 film, which was then cut into small discs with a diameter of 16 mm.

[0083] B. A method for preparing an ethanol aluminum composite polymer electrolyte membrane

[0084] S1. Under an inert atmosphere, TEGDA (mixed with 1 wt% of photoinitiator BAPO) and basic lithium battery electrolyte (1 mol LiPF6 in a mixed solution of EC, DMC and EMC (the volume ratio of EC: DMC: EMC is 1:1:1) are mixed at a ratio of 1.5:10 (w / w) and stirred overnight to form a uniform solution to obtain a photocurable precursor solution.

[0085] The mass ratio of TEGDA (mixed with 1 wt % of photoinitiator BAPO) to the basic electrolyte is 1.3:10.

[0086] S2. Inject 30 μL of photocurable precursor solution onto the Al(EtO)3 film and cure it under ultraviolet radiation for 20 seconds to obtain a composite polymer electrolyte (Al(EtO)3-TEGDA).

[0087] Example 4

[0088] A. Preparation method of Al(EtO)3 film

[0089] (1) 0.3 g of aluminum powder and 0.085 g of lithium powder were weighed and uniformly mixed in a graphite crucible to obtain a mixture; the mixture was placed in a muffle furnace, heated at 800° C. for 20 min, then quickly taken out and flattened with a graphite column, and cooled to obtain a LiAl alloy.

[0090] (2) Synthesis of Al(EtO)3: 0.115 g of LiAl alloy was reacted with 20 mL of anhydrous ethanol for 30 h to obtain a uniform Al(EtO)3 gel.

[0091] (3) The obtained gel was washed three times with 10 mL of anhydrous ethanol to remove soluble lithium ethoxide. 2 mL of the gel was taken and filtered to obtain a smooth Al(EtO)3 film, which was then cut into small discs with a diameter of 16 mm.

[0092] B. A method for preparing an ethanol aluminum composite polymer electrolyte membrane

[0093] S1. Under an inert atmosphere, ε-CL was mixed with a basic lithium battery electrolyte (1 mol LiTFSI in a mixed solution of EC and DEC (the volume ratio of EC:DEC was 1:1) at a ratio of 1:1 (w / w), and stirred overnight to form a uniform solution to obtain a photocurable precursor solution.

[0094] Among them, the mass ratio of ε-CL to the basic electrolyte is 1:1.

[0095] S2. Inject 20 μL of the photocuring precursor solution onto the Al(EtO)3 film and keep it in a 50°C constant temperature box for 4 hours to obtain a composite polymer electrolyte (AN-PCL).

[0096] Example 5

[0097] A. Grinding of commercial aluminum ethanol powder:

[0098] 1 g of aluminum ethoxide powder purchased from MacLean Reagent Network (Cat. No. A831038) was weighed into a mortar and ground for half an hour.

[0099] B. A method for preparing an ethanol aluminum composite polymer electrolyte membrane

[0100] S1. Under an inert atmosphere, TEPTA (mixed with 1 wt% of photoinitiator BAPO) and a basic sodium electrolyte (a mixed solution of 1 mol NaPF6 in Diglyme and ethanol aluminum powder at a ratio of 1.5:10:0.3 (w / w / w) were mixed and stirred overnight to form a uniform solution to obtain a photocurable precursor solution.

[0101] The mass ratio of TEPTA (mixed with 1 wt % of photoinitiator BAPO) to the basic electrolyte is 1.5:10.

[0102] S2. 30 μL of the photocurable precursor solution was added to the sodium metal negative electrode and cured by ultraviolet radiation for 20 seconds to obtain a composite polymer electrolyte (Al(EtO)3-TEPTA-Na).

[0103] Comparative Example 1

[0104] The difference from step A of Example 1 is that a step is added, specifically: the Al(EtO)3 film prepared in Example 1 is calcined at 800°C for 2h to obtain an aluminum oxide film (diameter 16mm).

[0105] Step B: A method for preparing an ethanol aluminum composite polymer electrolyte membrane

[0106] S1. Under an inert atmosphere, PEGDA (mixed with 1 wt% of photoinitiator BAPO) and basic lithium battery electrolyte (a mixed solution of 1 mol LiPF6 in EC, DMC and EMC (the volume ratio of EC: DMC: EMC is 1:1:1)) were mixed at a ratio of 1.5:10 (w / w) and stirred overnight to form a uniform solution to obtain a photocurable precursor solution.

[0107] S2. Inject 20 μL of the photocurable precursor solution onto the aluminum oxide film and cure it under ultraviolet radiation for 20 seconds to obtain a composite polymer electrolyte (Al2O3-PEGDA).

[0108] Comparative Example 2

[0109] Step B: A method for preparing an ethanol aluminum composite polymer electrolyte membrane

[0110] S1. Under an inert atmosphere, TEPTA was mixed with 1 wt% of a photoinitiator, BAPO, and a basic lithium battery electrolyte (1 mol of LiPF6 in a mixed solution of EC, DMC, and EMC (the volume ratio of EC: DMC: EMC was 1:1:1) at a ratio of 1.5:10 (w / w), and stirred overnight to form a uniform solution to obtain a photocurable precursor solution.

[0111] The mass ratio of TEPTA (mixed with 1 wt % of photoinitiator BAPO) to the basic electrolyte is 1.3:10.

[0112] S2. 30 μL of the photocurable precursor solution was added dropwise onto the lithium metal negative electrode and cured by ultraviolet radiation for 20 seconds to obtain a polymer electrolyte (GPE-TEPTA).

[0113] Comparative Example 3

[0114] Step B: A method for preparing an ethanol aluminum composite polymer electrolyte membrane

[0115] S1. Under an inert atmosphere, TEGDA was mixed with 1 wt% of a photoinitiator, BAPO, and a basic lithium battery electrolyte (1 mol of LiPF6 in a mixed solution of EC, DMC, and EMC (the volume ratio of EC: DMC: EMC was 1:1:1) at a ratio of 1.5:10 (w / w), and stirred overnight to form a uniform solution to obtain a photocurable precursor solution.

[0116] The mass ratio of TEGDA (mixed with 1 wt % of photoinitiator BAPO) to the basic electrolyte is 1.3:10.

[0117] S2. 30 μL of the photocurable precursor solution was added to the lithium metal negative electrode and cured by ultraviolet radiation for 20 seconds to obtain a polymer electrolyte (GPE-TEGDA).

[0118] Comparative Example 4

[0119] Step B: A method for preparing an ethanol aluminum composite polymer electrolyte membrane

[0120] S1. Under an inert atmosphere, TEPTA was mixed with 1 wt% of a photoinitiator, BAPO, and a basic sodium electrolyte (a mixed solution of 1 mol NaPF6 in Diglyme) at a ratio of 1.5:10 (w / w), and stirred overnight to form a uniform solution.

[0121] The mass ratio of TEPTA (mixed with 1 wt % of photoinitiator BAPO) to the basic electrolyte is 1.5:10.

[0122] S2. 30 μL of the photocurable precursor solution was added dropwise onto the sodium metal negative electrode and cured by ultraviolet radiation for 20 seconds to obtain a polymer electrolyte (GPE-TEPTA-Na).

[0123] Application Examples

[0124] The ethanol aluminum composite polymer electrolyte membranes prepared in Examples 1-5 and Comparative Examples 1-4 are used in assembled batteries, thus obtaining Application Examples 1-5 and Application Comparative Examples 1-4.

[0125] How to assemble the battery:

[0126] (1) combining the prepared ethanol aluminum composite polymer electrolyte membrane with a metal negative electrode;

[0127] (2) Using commercial cathode as cathode material;

[0128] (3) Assemble to obtain a full battery.

[0129] Among them, the positive electrodes of Examples 1-3 and Comparative Examples 1-3 use commercial NCM622, the positive electrode of Example 4 uses commercial LFP, and the positive electrode of Example 5 and Comparative Example 4 uses commercial NVP.

[0130] The preparation method of LiFePO4 (LFP) positive electrode sheet is specifically as follows:

[0131] (1) Mixing: LFP powder, acetylene black powder and PVDF powder were weighed in a mortar in a ratio of 7:2:1, and the three powders were manually ground for 30 min to mix them evenly. The powders were transferred to a glass bottle with a magnet, and N-methylpyrrolidone (NMP) was added and stirred at high speed for 4 h to form a slurry;

[0132] (2) Coating: After the slurry is stirred evenly, it can be coated on the coating machine. The positive electrode current collector uses flat aluminum foil. A scraper is used during the coating process to ensure the thickness and quality of the electrode is uniform. Finally, the coated electrode is placed in a vacuum drying oven at 80°C for 24 hours to remove the solvent. The dried electrode is cut into 10 mm discs. The active material loading is about 2 mg cm -2 .

[0133] The preparation method of NCM622 positive electrode sheet is specifically as follows:

[0134] (1) Mixing: Weigh NCM622 powder, acetylene black powder and PVDF powder in a mortar in a ratio of 8:1:1, grind by hand for 30 min to mix the three powders evenly, transfer the powders to a glass bottle with a magnet, add N-methylpyrrolidone (NMP) and stir at high speed for four hours to form a slurry;

[0135] (2) Coating: After the slurry is stirred evenly, it can be coated on the coating machine. The positive electrode current collector uses flat aluminum foil. A scraper is used during the coating process to ensure the thickness and quality of the electrode is uniform. Finally, the coated electrode is placed in a vacuum drying oven at 80°C for 24 hours to remove the solvent. The dried electrode is cut into 10 mm discs. The active material loading is about 2 mg cm -2 .

[0136] The preparation method of Na3V2(PO4)3(NVP) positive electrode sheet is specifically as follows:

[0137] (1) Mixing: Weigh NVP powder, acetylene black powder and PVDF powder in a mortar according to a ratio of 7:2:1, grind them manually for 30 minutes to mix the three powders evenly, transfer the powders to a glass bottle with a magnet, add N-methylpyrrolidone (NMP) and stir at high speed for 4 hours to form a slurry.

[0138] (2) Coating: After the slurry is stirred evenly, it can be coated on the coating machine. The positive electrode current collector uses flat aluminum foil. A scraper is used during the coating process to ensure the thickness and quality of the electrode. Finally, the coated electrode is placed in a vacuum drying oven at 80°C for 24 hours to remove the solvent. The dried electrode is cut into 10mm discs. The active material loading is about 2mgcm -2 .

[0139] The specific method of assembling the battery is as follows: the battery shell (model CR2032) is composed of a negative electrode shell, a positive electrode shell, a spring and a gasket. From bottom to top, it is the positive electrode shell, the positive electrode material, the ethanol aluminum composite polymer electrolyte, the negative electrode material, the stainless steel gasket, the spring and the negative electrode shell. Finally, the battery is moved to the sealing machine with insulated tweezers to seal the battery.

[0140] Effect Experiment

[0141] Test the stability of assembled batteries:

[0142] Experimental methods

[0143] Battery constant current charge and discharge test: Use the LAND CT2001A battery test system to apply a specific current to the assembled button cell, and monitor and record the voltage change over time. The battery capacity, long cycle stability, rate, coulomb efficiency and other performance parameters can be obtained. The batteries of the application examples and the comparative examples are all tested at 30°C.

[0144] Experimental results analysis

[0145] Depend on Figure 1 It can be seen that in Example 1, the Li|Al(EtO)3-PEGDA|NCM622 battery was used for cycle testing, and the capacity was 127 mAh g after 150 cycles.-1 , the capacity retention rate is 89%.

[0146] Depend on Figure 2 It can be seen that in Example 2, the Li|Al(EtO)3-TEPTA|NCM622 battery was used for cycle testing, and the capacity was 158 mAh g after 100 cycles. -1 , the capacity retention rate is 80%.

[0147] Depend on Figure 3 It can be seen that in Example 3, the Li|Al(EtO)3-TEGDA|NCM622 battery was used for cycle testing, and the capacity was 122 mAh g after 90 cycles. -1 , the capacity retention rate is 98%.

[0148] Depend on Figure 4 It can be seen that in Example 4, the Li|AN-PCL|LFP battery was used for cycle testing, and the capacity was 98 mAh g after 75 cycles. -1 .

[0149] Depend on Figure 5 It can be seen that in Example 5, the Na|Al(EtO)3-TEPTA-Na|NVP battery was used for cycle testing, and the capacity retention rate was as high as 92% after 500 high-rate 25C cycles.

[0150] Comparative Example 1 used Li|Al2O3-PEGDA|NCM622 battery for cycle testing. After 3 cycles, the battery failed and could not be charged and discharged normally ( Figure 1 ).

[0151] Comparative Example 2 uses Li|GPE-TEPTA|NCM622 battery for cycle testing. After 100 cycles, the capacity decays to 61 mAh g -1 , the capacity retention rate is only 69% ( Figure 2 ).

[0152] Comparative Example 3 uses Li|GPE-TEGDA|NCM622 battery for cycle testing. After 90 cycles, the capacity decays to 119 mAh g -1 , the capacity retention rate is only 92% ( Figure 3 ).

[0153] Comparative Example 4 used Na|GPE-TEPTA-Na|NVP battery for cycle testing. After 355 cycles, the battery failed and could not be charged and discharged normally ( Figure 5 ).

[0154] In summary, it can be seen from the application comparison examples 2-4 that, compared with the simple composite polymer electrolyte membrane, the electrolyte membrane obtained by combining the composite polymer with ethanol aluminum can make the battery cycle stability better; from the application comparison example 1, it can be seen that the electrolyte membrane obtained by combining ethanol aluminum with the composite polymer has better cycle stability than the electrolyte membrane obtained by combining Al2O3 with the composite polymer.

[0155] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An ethanol aluminum composite polymer electrolyte membrane, characterized in that: The aluminum ethoxide composite polymer electrolyte membrane comprises a polymer and aluminum ethoxide; The polymer is a polymer containing an ester group and / or an ether bond in its structure; the polymer is polyethylene oxide or a polyethylene oxide derivative; the polyethylene oxide derivative is obtained from a small molecule monomer through photopolymerization; the ethanol aluminum can be obtained through commercial purchase or self-preparation.

2. The ethanol aluminum composite polymer electrolyte membrane according to claim 1, characterized in that The small molecule monomer is selected from one or more of polyethylene glycol diacrylate, triethylene glycol diacrylate, polyethylene glycol diacrylate, tetraethylene glycol diacrylate, 1,3-dioxolane, polyethylene glycol dimethyl ether, ε-caprolactone and ethoxylated trimethylolpropane triacrylate.

3. The method for preparing the ethanol aluminum composite polymer electrolyte membrane according to any one of claims 1 or 2, characterized in that: The steps include: A. Synthesis of Aluminum Ethanol Film (1) Aluminum powder and metal powder are mixed and melted to obtain molten alloy sheets; (2) cooling the alloy sheet in step (1), and then reacting with anhydrous ethanol to obtain ethanol aluminum gel; (3) washing the byproducts and filtering the ethoxide aluminum gel obtained in step (2) to obtain an ethoxide aluminum film; B. Synthesis of Aluminum Ethoxide Composite Polymer Electrolyte Membrane S1. In an inert atmosphere, a polymer monomer is mixed with a photoinitiator to obtain a mixed solution, and then the mixed solution is mixed and stirred with a basic electrolyte or an electrolyte salt to obtain a photocurable precursor solution; S2. Placing the aluminum ethanol film obtained in step A on the negative electrode, dripping the photocurable precursor solution obtained in step S1, and irradiating with ultraviolet light or drying to obtain the aluminum ethanol composite polymer electrolyte membrane.

4. The preparation method according to claim 3, characterized in that: B. The mass fraction of the photoinitiator in step S1 in the monomer is 1-10 wt %.

5. The preparation method according to claim 3, characterized in that: B. The basic electrolyte described in step S1 includes an electrolyte salt and a solvent; the weight ratio of the mixed solution to the basic electrolyte is 1-10:

10.

6. Use of the ethoxide aluminum composite polymer electrolyte membrane according to any one of claims 1 or 2 or the ethoxide aluminum composite polymer electrolyte membrane obtained by the preparation method according to any one of claims 3 to 5 in preparing a battery.

7. A battery, characterized in that: The invention comprises the ethanol aluminum composite polymer electrolyte membrane as described in any one of claims 1 or 2 or the ethanol aluminum composite polymer electrolyte membrane obtained by the preparation method as described in any one of claims 3-5.

8. The battery according to claim 7, characterized in that The battery is a lithium battery or a sodium battery.

9. The battery according to claim 7, characterized in that The battery consists of a negative electrode, an ethanol aluminum composite polymer electrolyte membrane and a positive electrode.

10. The battery assembly process according to any one of claims 7 to 9, characterized in that: The steps include: (1) combining the prepared ethanol aluminum composite polymer electrolyte membrane with the negative electrode; (2) Using commercial cathode as cathode material; (3) Assemble and obtain the battery.

Citation Information

Patent Citations

  • Polymer solution, gel electrolyte, sodium ion battery, gel polymer diaphragm and preparation method

    CN117467164A

  • Polymer electrolyte membrane and preparation method thereof, and polymer cell

    CN102117932A

  • Preparation method of LiAl5O8 nanowire, composite solid electrolyte and lithium metal battery

    CN112701344A

  • Al-centered polymer electrolyte and preparation method and application thereof

    CN112993393A

  • Aluminum atom doped PEG-based polymer electrolyte and preparation method and application thereof

    CN116053701A